(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper we shall study on the some famed history and integer solution of some Diophantine Equations in +ve integer solution and connection with Pythagorean triples and Pell’s Equation. We have shown that how some solution can be found with the help of conversion into Diophantine equation.